"Rule of Trust": The power and perils of China's social credit megaproject - CHEN, Yu-Jie (Institutional Knowledge at Singapore Management University, 2018)
Emerging as a comprehensive and aggressive governance scheme in China, the “Social Credit System” (SCS) seeks to promote the norms of “trust” in the Chinese society by rewarding behavior that is considered “trust-keeping” and punishing those considered “trust-breaking.” This Article closely examines the evolving SCS regime and corrects myths and misunderstandings popularized in the international media. We identify four key mechanisms of the SCS, i.e., information gathering, information sharing, labeling, and joint sanctions, and highlight their unique characteristics as well as normative implications. In our view, the new governance mode underlying the SCS—what we call the “rule of trust”—relies on the fuzzy notion of “trust” and wide-ranging arbitrary and disproportionate punishments. It derogates from the notion of “governing the country in accordance with the law” enshrined in China’s Constitution.This Article contributes to legal scholarship by offering a distinctive critique of the perils of China’s SCS in terms of the party-state’s tightening social control and human rights violations. Further, we critically assess how the Chinese government uses information and communication technologies to facilitate data-gathering and data-sharing in the SCS with few meaningful legal constraints. The unbounded and uncertain notion of “trust” and the unrestrained employment of technology are a dangerous combination in the context of governance. We conclude with a caution that with considerable sophistication, the Chinese government is preparing a much more sweeping version of SCS reinforced by artificial intelligence tools such as facial-recognition and predictive policing. Those developments will further empower the government to enhance surveillance and perpetuate authoritarianism.